Development of ecotourism sustainability assessment framework employing Delphi, C&I and participatory methods: A case study of KBR, West Sikkim, India. (January 2017) - Ashok, Smriti; Tewari, H.R.; Behera, M.D.; Majumdar, Arijit
Abstract: This paper proposes an assessment of "Ecotourism Sustainability" at an operational level utilizing Principles-Criteria-Indicators-Verifiers, common in forest and tourism sustainability evaluation. Initially criteria were identified based on a literature review. This was followed by a Delphi Study and Participatory Workshops in Sikkim, India. Finally expert opinions were elicited. 4 principles, 8 criteria, 58 indicators and their corresponding 58 verifiers were established and measures of agreement calculated across different prior stages. From these a framework of analysis for assessing sustainability at an operational level in ecotourism was then established. Highlights: A framework based on Principles-Criteria-Indicators-Verifiers (PCIV) is developed for assessment of "Ecotourism Sustainability". Literature Review, Delphi Study & Participatory Workshops were used to derive PCIV. Analysis led to 4-Principles, 8-Criteria, 58-Indicators and respective 58-Verifiers. Using Goodness-of-Fit test the Principles and their Criteria were made operational. The framework can assess degree of ecotourism sustainability at operational level.